A Brief Gramscian Analysis of the First Five Years of the AKP: How the Organic Intellectuals of Turkey Helped Cement the Power of Erdoğan and his Party - Çakir, Can (Satura, 2018)
In this paper, I will try to underline the role of intellectuals in Turkey during President Recep Tayyip Erdoğan’s first five years as Prime Minister in establishing his hegemony. The analysis will be conducted using a Gramscian approach. I will begin the paper by presenting the framework. I will give a brief definition of the concepts called organic intellectuals and historical bloc, coined by the Italian Marxist theorist Antonio Gramsci. Following the theoretical introduction, I will give empirical evidence, using excerpts from articles and interviews of three prominent intellectuals2 who are known as the Birikim troika in the Turkish academic and journalistic sphere. It is worth noting that two out of the three writers included in the paper were well-known full professors of economics and comparative literature in Galatasaray University and Istanbul Bilgi University, respectively.